Hysteresis current control for single-phase transformerless inverter - Mohd Azhar, Aina Suhailah; Azri, Maaspaliza; Abd Halim, Wahidah; Talib, Md Hairul Nizam; Rasin, Zulhani; Mohammed, Mohd Fayzul (Institute of Advanced Engineering and Science, 2025)
The total harmonic distortion (THD) of grid current and leakage current are significant for transformerless inverters, as they impact power quality, efficiency, and compliance with grid codes. Monitoring and minimizing these currents ensure safe and reliable grid integration of photovoltaic (PV) systems while reducing electromagnetic interference. Therefore, in this paper, the analysis THD of grid current and leakage current is described. The bipolar pulse width modulation (BPWM) technology provides a stable common-mode voltage (200 V), fewer leakage currents (< 30 mA), and better system efficiency, compared to the unipolar pulse width modulation (UPWM) technique. To ensure the inverter complies with the IEC 61000-3-2 class C (THDi < 5%), the current control strategy should be considered during the design of the transformerless inverter. Therefore, this paper presents an implementation and evaluation of the bipolar hysteresis current control (BHCC) technique. In comparison to the BPWM technique, the BHCC technique delivers lower leakage current (0.007274 A), reduced grid current harmonic distortion (1.81%), and increased efficiency.